Clinical handover in a bilingual setting: interpretative phenomenological analysis to exploring translanguaging practices for effective communication among hospital staff - Jack Pun (BMJ Open)
Objective To explore the linguistic features of translanguaging in bilingual handover practices and elicit the views of hospital staff on factors that hinder or facilitate effective handover practice in a bilingual environment.Methods 78 hospital staff were recruited from hospital wards and emergency departments of two Hong Kong hospitals. They were interviewed to determine their perceptions of their handover communication in a bilingual context, and their responses were subjected to interpretative phenomenological analysis.Results Based on the staff interviews, three dimensions with potential applications to effective clinical handover are identified. A revised Identify, Situation, Background, Assessment and Recommendation protocol accounting for linguistic pluralism (i.e., the translanguaging process) is suggested to underpin the future research agenda around effective clinical communication in a bilingual context.Conclusions Research on handover communication in multilingual contexts is limited. This study outlines linguistic pluralism at the handover stage and details the complexity of handover communication for staff in a bilingual context. It urges for more research with a specific focus on identifying avoidable linguistic issues that emerge from the clinical context and developing a suitable protocol to standardise staff’s translanguaging processes to ensure a safe and efficient handover process in a bilingual environment.